The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/2013jc009070
|View full text |Cite
|
Sign up to set email alerts
|

The influence of an Antarctic glacier tongue on near-field ocean circulation and mixing

Abstract: In situ measurements of flow and stratification in the vicinity of the Erebus Glacier Tongue, a 12 km long floating Antarctic glacier, show the significant influence of the glacier. Three ADCPs (75, 300, and 600 kHz) were deployed close (<50 m) to the sidewall of the glacier in order to capture near-field flow distortion. Scalar (temperature and conductivity) and shear microstructure profiling captured small-scale vertical variability. and a background/residual flow ($4-10 cm s 21 ) flowing to the NW. Turbulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 38 publications
(83 reference statements)
1
25
0
Order By: Relevance
“…The eastern side of the sound is generally thought to flow southward (Robinson and Williams, 2012). However, observations close to shore indicate a northward flow suggesting there might be flow separation around Tent Island and so flowing back towards the NW (Leonard et al, 2006;Stevens et al, 2013). Such currents were observed in observations near the EGT tip in 2010 (Stevens et al, 2013).…”
Section: Calvingmentioning
confidence: 98%
See 1 more Smart Citation
“…The eastern side of the sound is generally thought to flow southward (Robinson and Williams, 2012). However, observations close to shore indicate a northward flow suggesting there might be flow separation around Tent Island and so flowing back towards the NW (Leonard et al, 2006;Stevens et al, 2013). Such currents were observed in observations near the EGT tip in 2010 (Stevens et al, 2013).…”
Section: Calvingmentioning
confidence: 98%
“…2a, b). GPS transects of glacier freeboard from December 2010 indicate that these depressions imply a marked localized thinning of the glacier (Stevens et al, 2013).…”
Section: Calvingmentioning
confidence: 99%
“…The observed staircase had a statically stable configuration of relatively warm, fresh water overlying cold, salty water, which is not susceptible to diffusive convection but to differential diffusion. Stevens et al (2014) argues that the layers observed beside the Erebus Glacier Tongue might have formed as a result of shear-driven instability, where the shear is caused by flow over nearby bottom topography. There are no similar topographic features near our drilling sites.…”
Section: Observationsmentioning
confidence: 99%
“…At the mast site, during the measurement period, profiles made with the mobile TIC Mast B indicated that the water column was isothermal to about 40 m. In addition, data described in Stevens et al (2014) from the same campaign support the contention that, to within ±5 mK, the upper 40 m was isothermal. The upper 15 m exhibited temperatures below the pressure-dependent freezing temperature, i.e.…”
Section: Resultsmentioning
confidence: 59%
“…The general layout of EFC and its location relative to nearby geographic features is described by Stevens et al (2014Stevens et al ( , 2011 and shown in Fig. 2.…”
Section: Field Camp and Instrumentationmentioning
confidence: 99%